Phenomenology-Based Accounting for Cultural Heritage Assets: Interpreting the Economic and Cultural Value of the Tokko Garment - Muhammad Abrar; Muhammad Yamin; Evi Irawati Aisya.A; A.Syalfana Muthia Reski Amelia Putri (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study explores the lived experiences of cultural actors regarding the Tokko garment in Bone Regency, South Sulawesi, employing a qualitative phenomenological approach to examine its multi-dimensional value and reporting practices. Traditional figures, garment artisans, and community members reveal that the garment encapsulates deep historical lineage, philosophical chromatic symbolism, social solidarity, spiritual sanctity, and economic utility. Findings indicate that conventional monetary valuation fails to capture these intangible heritage attributes, creating significant reporting anomalies within institutional accounting systems. To resolve this limitation, the research proposes a comprehensive recognition and disclosure framework that accommodates non-monetary values through detailed narrative disclosures of provenance, symbolic meanings, physical conditions, and preservation efforts. Ultimately, this integration of phenomenology and cultural accounting bridges financial governance with indigenous heritage preservation, providing a robust model for reporting culturally significant assets.